Investing in Madagascar and Exploring Trends in Business, Services, and Financial Development - Rakotoniriana Noelisoa Jean Michel; Razafitahindraza Erica Feyzine Sulla; Hangivola Emyblonde Ratna (Bisnis, Jasa dan Keuangan, 2026)
This study examines investment dynamics and emerging trends in business, service sector development, and financial systems in Madagascar, with the aim of understanding how these elements interact to shape economic transformation. Using a qualitative approach, data were collected from 35 key informants representing public institutions, private enterprises, financial services, and development organizations. The findings reveal that investment plays a central role in driving economic activity; however, its impact remains uneven across sectors and regions, with a strong concentration in export-oriented agriculture and selected urban services. Entrepreneurial activity is expanding, yet it continues to face significant structural barriers, including limited access to finance, regulatory challenges, and weak infrastructure. The service sector shows gradual growth, particularly through digital financial services such as mobile money, which have improved financial inclusion, although the depth and diversity of services remain limited. The study also highlights the importance of governance and decentralization in shaping investment outcomes, with inconsistent implementation affecting efficiency and accountability. Furthermore, sectoral dependency on primary commodities increases vulnerability to external shocks, while digital transformation emerges as a promising but underutilized driver of service sector development. The study concludes that Madagascar’s economic progress is constrained by structural and institutional challenges, requiring coordinated efforts to enhance infrastructure, strengthen financial systems, promote diversification, and support digital adoption. These findings provide important insights for policymakers and stakeholders seeking to foster inclusive and sustainable economic development